Avoiding Neurovascular Risk During Percutaneous Clamp Reduction of Spiral Tibial Shaft Fractures: An Anatomic Correlation With Computed Tomography. Issue 9 (September 2018) - Horrigan, Patrick B.; Coughlan, Monica J.; DeBaun, Malcolm R.; Schultz, Blake; Bishop, Julius A.; Gardner, Michael J.
Abstract : Summary: The use of percutaneous clamps is often a helpful tool to aid reduction and intramedullary nailing of distal tibial spiral diaphyseal fractures. However, the anterior and posterior neurovascular bundles are at risk without careful clamp placement. We describe our preferred technique of percutaneous clamp reduction for distal spiral tibial fractures with a distal posterolateral fracture spike, with care to protect the adjacent neurovascular structures. We also investigated the relationship between these neurovascular structures and the site of common percutaneous clamp placement. Preoperative computed tomography images of surgically managed patients who sustained this specific common fracture pattern (distal third spiral diaphyseal tibia fracture with a posterolateral fragment) were retrospectively reviewed. On computed tomography, we extrapolated the ideal virtual clamp site on the posterolateral fracture fragment to facilitate reduction. The average distance of this clamp position from the anterior neurovascular bundle was 14 mm (SD = 7.6), with a range of 6–32 mm. The average distance of the clamp site from the posterior neurovascular bundle was 19 mm (SD = 6.1), with a range of 11–30 mm. In 31% of patients, the distal fragment's apex extended anterior to the interosseous membrane, and in 69% of patients, the apex was posterior to the interosseous membrane. We also describe our preferred surgical technique with percutaneous clamping and tibial nailing, which involves sliding the posterolateral tine of the percutaneous clamp along the lateral tibial cortex to prevent neurovascular bundle injury. Abstract : Supplemental Digital Content is Available in the Text.